Electrogustometry: Normative data for stimulus duration, tongue site and age decline. (19th February 2021) - Pavlidis, Pavlos; Schittek, Gregor Alexander; Saratziotis, Athanasios; Ferfeli, Maria; Kekes, Georgios; Gouveris, Haralampos
Abstract: Objectives: Our primary goal was to evaluate the effect of stimulus duration on electrogustometry (EGM) thresholds. Additionally, we sought to evaluate any sex‐related influences and compare the above results to those of taste strips. Design: Electrogustometry thresholds of various stimulus durations (0.5, 1.0, 1.5 and 2.0 seconds) were measured in 212 non‐smokers (age range: 10‐80 years, divided into eight age‐groups) without self‐reported gustatory impairment. Furthermore, taste strips chemogustometry measurements in 132 participants were performed. Setting: Tertiary referral medical centre. Participants: 212 non‐smokers, divided into eight age‐groups participated in the study. Main outcome measures: Electrogustometry thresholds and taste strips, duration of EGM stimuli. Results: Electrogustometry thresholds increased progressively with age and with stimulus duration from 0.5 to 2 seconds. This pattern was consistent in all six anatomic areas, irrespective of sex. In contrast, when using chemogustometry, no age‐ or sex‐related differences were observed. Conclusions: Electrogustometry‐threshold values increase progressively with age and with stimulus duration. Therefore, we recommend documenting stimulus duration in the future EGM recordings as it may significantly affect EGM amplitude threshold values.